RECOVERY OF LITHIUM AND OTHER METALS FROM THE SCRAP OF SPENT LITHIUM BATTERIES - Kolobov , German; Kirichenko , Oleksii; Mosejko , Yuriy; Pavlov , Vasyl; Panova , Vira; Pecheritsa , Konstantin; Bubinetts , Alexey (Scientific Journal "Metallurgy", 2020)
In paper, the technologies used to recovery lithium and other metals from the scrap of spent lithium batteries are reviewed. To solubilize lithium and other metals, aqueous or acid leaching (sometimes bioleaching) of pre-ground scrap is used. Metals are recovered from the solution by methods of chemical deposition (including hydrolysis, electrodeposition, extraction using extractants N1923, PAN, 1N2N, Cyanex 272); ion exchange on sorbents Amberlite IR120, molecular sieve 13X, aluminosilicate MCM41, activated carbon; electrodialysis using bipolar membranes. For the processing of scrap of lithium storage batteries, such pyrometallurgical methods as pyrolysis and melting are also used. Because lithium batteries have received unprecedented development in recent years, most new recycling work for lithium-containing recyclable materials is dedicated to the recycling of waste lithium batteries, which is a valuable secondary resource for removing lithium and other metals. This paper reviews the technologies used to extract lithium and other metals (cobalt, nickel, copper, manganese) from scrap waste lithium batteries. To convert lithium and other metals into solution water or acid leaching (hydrochloric, sulfuric, ascorbic acids), sometimes bioleaching of pre-crushed scrap are used. Metals are recovered from the solution by chemical precipitation (including hydrolysis; electrodeposition; extraction using N1923, PAN, 1N2N, Cyanex 272 extractants); ion exchange on sorbents (Amberlite IR120, molecular sieve 13X, aluminosilicate MSM41, activated carbon); electrodialysis using bipolar membranes. Pyrometallurgical methods such as pyrolysis and melting are also used to process lithium battery scrap. The melting of lithium battery scrap forms a slag consisting of aluminum, calcium, lithium, magnesium, manganese and silicon oxides. An important task is to select a slag of such composition that the maximum amount of lithium is concentrated in the LiAlO2 compound. The possibility of obtaining aluminum and magnesium silicate of lithium is shown, in which the content of lithium is 10 %, while in the spodumene it is 3.7 %. Such slag can be enriched by flotation using collectors for oxide minerals. At rapid cooling of the slag, its structure is crushed and lithium can be removed by hydrometallurgical method.